2021
DOI: 10.3390/jmse9010072
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Sensitivity/Vulnerability Characterization and Adaptation Strategies: A Review

Abstract: Coastal area constitutes a vulnerable environment and requires special attention to preserve ecosystems and human activities therein. To this aim, many studies have been devoted both in past and recent years to analyzing the main factors affecting coastal vulnerability and susceptibility. Among the most used approaches, the Coastal Vulnerability Index (CVI) accounts for all relevant variables that characterize the coastal environment dealing with: (i) forcing actions (waves, tidal range, sea-level rise, etc.),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 158 publications
(253 reference statements)
1
43
0
1
Order By: Relevance
“…With these comparative results, it was possible to demonstrate the adaptability of the CMI to assess coastal risks with basic information, and quickly [13,29,96,97], contrary to other indices that require very specific information from each site, which is expensive to obtain [49,[98][99][100][101][102][103][104][105][106]. We agree with authors [107,108] who have explained the importance of choosing and implementing specific actions in each polygon according to the communities' needs and vulnerabilities.…”
Section: Discussionsupporting
confidence: 62%
“…With these comparative results, it was possible to demonstrate the adaptability of the CMI to assess coastal risks with basic information, and quickly [13,29,96,97], contrary to other indices that require very specific information from each site, which is expensive to obtain [49,[98][99][100][101][102][103][104][105][106]. We agree with authors [107,108] who have explained the importance of choosing and implementing specific actions in each polygon according to the communities' needs and vulnerabilities.…”
Section: Discussionsupporting
confidence: 62%
“…The important policy, planning, practice and programs for CCA and DRR are revealed. Anfuso et al (2021) 205 published articles were reviewed and the authors examined the different vulnerability indexes, built up with forcing and morphological variables in both coastal sensitivity and vulnerability studies, together with the main coastal adaptation strategies used to reduce biophysical vulnerability. The analysis demonstrated that the more sophisticated the index or the model, the more data are required, so this point highlights the need for observations, continuous measurements and open-access databases.…”
Section: Busayo Et Al (2020)mentioning
confidence: 99%
“…Most of the understanding of episodic erosion phenomena is based on statistical analysis of beach erosion survey data or numerical model results that rely on physical parameters related to the sediment process (Mendoza and Jimeńez, 2006;Bosom and Jimeńez, 2011;Oliveira et al, 2014;Ballesteros et al, 2017;Narra et al, 2019;Anfuso et al, 2021). Data analysis has been mainly used for the purpose of finding long-term erosion rates, and short-term erosion has recently become possible with the analysis of CCTV image data.…”
Section: Introductionmentioning
confidence: 99%